A fuzzy nonparametric Shewhart chart based on the bootstrap approach - Wang, Dabuxilatu; Hryniewicz, Olgierd (1948- ) (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, we consider a nonparametric Shewhart chart for fuzzy data. We utilize the fuzzy data without transforming them into a real-valued scalar (a representative value). Usually fuzzy data (described by fuzzy random variables) do not have a distributional model available, and also the size of the fuzzy sample data is small.
Keywords: Shewhart control chart; fuzzy data; bootstrap; average run length